Cavity-mediated collective laser-cooling of a non-interacting atomic gas inside an asymmetric trap to very low temperatures. Issue 5 (30th March 2018) - Kim, Oleg; Deb, Prasenjit; Beige, Almut
Abstract : In this paper, we identify a many-particle phonon expectation valueζ with the ability to induce collective dynamics in a non-interacting atomic gas inside an optical cavity. We then propose to utilise this expectation value to enhance the laser cooling of many atoms through a cyclic two-stage process which consists of cooling and displacement stages. During cooling stages, short laser pulses are applied. These useζ as a resource and decrease the vibrational energy of the atomic gas by a fixed amount. Subsequent displacement stages use the asymmetry of the trapping potential to replenish the many-particle phonon expectation valueζ . Alternating both stages of the cooling process is shown to transfer the atomic gas to a final temperature which vanishes in the infinitely-many particle limit.